PENGARUH KONDISI KEUANGAN, OPINI AUDIT TAHUN SEBELUMNYA, AUDIT TENURE DAN AUDIT DELAY TERHADAP OPINI AUDIT GOING CONCERN - Suryani (Nusantara Hasana Journal, 2023)
This research aims to determine the effect of financial condition, previous year’s audit opinion, audit tenure, and audit delay on going concern audit opinion. The population in this research is used secondary data from the financial statement of manufacturing companies in the basic and chemical industry sectors listed on the Indonesia Stock Exchange period 2017-2021 as many as 19 companies. This research used purposive sampling method and obtained as many as 95 data used as research samples. The data analysis used logistic regression analysis with SPSS version 26 program. The result of this research show that financial condition and previous year’s audit opinion has a significant negative effect on going concern audit opinion. While the audit tenure and audit delay have no effect on going concern audit opinion.